INTESTINAL MICROBIOTA AND ITS EFFECTS ON THE FUNCTION OF SHAPED ELEMENTS IN FREQUENTLY ILL CHILDREN - Munira F. Usmanova; Khiromon N. Sirojiddinova (Central Asian Journal of Medicine, 2025)
The article presents the data of 146 frequently ill children aged from 1 to 6 years with respiratory diseases hospitalized in the No. 1 of Samarkand. As a comparison group, 30 episodically ill children were examined. The composition of the intestinal microflora, hematological parameters of blood and the adsorption capacity of erythrocytes were studied. The results of the study show that with severe diarrhea, as a complication of the underlying disease in FICh, hemolytic flora increases in the intestinal microflora, among which staphylococci occupy the first place, escherichia coli takes the second place and yeast-like fungi take the third.